KERATUAN MELINTING SEBAGAI SUMBER PEMBELAJARAN SEJARAH LOKAL DI SMA NEGERI 1 MELINTING LAMPUNG TIMUR - Tuti Alwiyah; Bobi Hidayat (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The research objectives are (1) to describe the history of the Melinting Keratuan in Marga Melinting East Lampung (2) to describe the utilization of the Melinting Keratuan as a source of local history learning in SMA Negeri 1 Melinting, East Lampung. This research method is descriptive qualitative. Data and data sources obtained from books, traditional leaders and village community leaders as sources, documentation and other sources that can help in gathering research data information. The results of this study are (1) Keratuan Melinting namely the local history of the Melinting area of East Lampung Regency, the history of the descendants of Queen Melinting cannot be separated from the history of Queen Putih's bloodline, because Ratu Melinting and Ratu Darah Putih are cousins who are descendants of Keratuan in Pugung (2) before carrying out learning in the classroom the first teacher conducted by the teacher is to determine KI and KD with material related to the use of the Melinting Unit, designing methods, making lesson plans, preparing media and questions. Furthermore, implementing it into learning activities carried out through the three stages of the first activity is the initial activity (greetings, apesepsi, then deliver KI, KD, indicators and learning objectives), core activities (exploration, elaboration and confirmation), and final activities (conclusions and reflections).